Patterns of alcohol consumption after liver transplantation. Issue 1 (1st July 1998) - Tang, H; Boulton, R; Gunson, B; Hubscher, S; Neuberger, J
Abstract : Background —Uncertainty exists about the extent and consequences of a return to alcohol consumption after liver transplantation for alcoholic liver disease (ALD). Aims —To determine the prevalence and consequences of alcohol consumption in patients transplanted for ALD. Methods —A retrospective case controlled study of all patients transplanted for ALD at the Queen Elizabeth Hospital, Birmingham, between 1987 and 1996. Results —Seventy patients with ALD were transplanted, of which 59 survived more than three months; 56 were interviewed. Twenty eight had consumed some alcohol after transplantation; for the nine "heavy drinkers" (HD), the median time to resumption of alcohol intake was six months and for the 19 "moderate drinkers" (MD) it was eight months. There was no significant difference in episodes of acute rejection or compliance with medication between those who were abstinent, MD, or HD. Histological evidence of liver injury was common in ALD patients who had returned to drink. Mild fatty change was found in 1/11 biopsy specimens from abstinent patients but moderate to severe fatty change and ballooned hepatocytes were seen in 3/5 MD and 2/5 HD specimens. Two HD patients had early fibrosis. One HD patient has died of alcohol related complications. Conclusions —Moderate to heavy alcohol consumption occurs in patients transplanted for ALD. Patient recall of abstinence advice is unreliable, and patients return to alcohol mainly within the first year after liver transplantation. Return to alcohol consumption after liver transplantation is associated with rapid development of histological liver injury including fibrosis.